3D Printed MXene Aerogels with Truly 3D Macrostructure and Highly Engineered Microstructure for Enhanced Electrical and Electrochemical Performance. Issue 2 (10th November 2021) - Tetik, Halil; Orangi, Jafar; Yang, Guang; Zhao, Keren; Mujib, Shakir Bin; Singh, Gurpreet; Beidaghi, Majid; Lin, Dong
Abstract: Assembling 2D materials such as MXenes into functional 3D aerogels using 3D printing technologies gains attention due to simplicity of fabrication, customized geometry and physical properties, and improved performance. Also, the establishment of straightforward electrode fabrication methods with the aim to hinder the restack and/or aggregation of electrode materials, which limits the performance of the electrode, is of great significant. In this study, unidirectional freeze casting and inkjet‐based 3D printing are combined to fabricate macroscopic porous aerogels with vertically aligned Ti3 C2 T x sheets. The fabrication method is developed to easily control the aerogel microstructure and alignment of the MXene sheets. The aerogels show excellent electromechanical performance so that they can withstand almost 50% compression before recovering to the original shape and maintain their electrical conductivities during continuous compression cycles. To enhance the electrochemical performance, an inkjet‐printed MXene current collector layer is added with horizontally aligned MXene sheets. This combines the superior electrical conductivity of the current collector layer with the improved ionic diffusion provided by the porous electrode. The cells fabricated with horizontal MXene sheets alignment as current collector with subsequent vertical MXene sheets alignment layers show the best electrochemical performance with thickness‐independent capacitive behavior. Abstract : A 3D printing method based on inkjet printing and unidirectional freeze casting is utilized to fabricate pristine Ti3 C2 T x aerogels with truly 3D shapes and vertically aligned MXene sheets. 3D printed aerogels are proposed for flexible/wearable electronics due to their excellent electromechanical performance. Enhanced electrochemical performance of the micro‐supercapacitors is attributed to the improved electrical conductivity and ionic diffusion achieved simultaneously.